Narrations on madness and sex. Differences between masculine and feminine ways of constructing autopatography in English language literature - Szmigiero, Katarzyna (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
Among the great variety of texts belonging to the life-writing category, patographies or illness narratives stand out as unique. The rising popularity of the genre can be explained by the humanisation of modern medicine and the unwillingness of contemporary culture to cope with suffering, ugliness and disability. Despite its private, or even confessional, nature patographies play important social roles: raise the readers’ awareness, push for reforms in health care and recommend treatments seen by their writers as beneficial. The aim of this article is to have a closer look at autobiographies written by English-speaking men and women who received a psychiatric diagnosis. Their accounts drastically differ depending on gender. Women construct their stories differently, defining exceptional or outstanding events in a different way. They are more willing to admit to failures but also pay more attention to cultural and social aspects of mental disorders. Men tend to accept a biomedical explanation of their illness and focus on their public activity after recovery.